Gamification and Learners’ Motivation in the New Normal - Julie Claire Lebuna; Erroll John Elloran; Reymond Losañes; Regine Genegaban; Jo Persi Solinap; Ramsene Janne Gotera; Crisia Mae Gemarino; Ralph Bryan Geca; Ariane Marie Nicmic (IC-ITECHS, 2022)
In the 21st century, the use of game-based and digital-based teaching methods is required. This descriptive research study aimed to determine the effects of gamification strategies on learners’ motivation in the New Normal. Specifically, it aimed to identify the dominant gamification strategies employed by college professors and determine the extent of their utilization . It will also discuss the learners’ level of motivation when gamification is utilized and if there is a significant relationship between the extent of utilization of gamification strategies and learners’ motivation. The respondents were the 103 Teacher Education students of Iloilo Science and Technology Miagao Campus who were exposed to gamification in the 2nd semester, 2021–2022. A descriptive survey-questionnaire was administered to collect the data . The result showed that Kahoot, Quizlet, and Quizizz are the three dominant gamification tools used by college professors teaching Teacher Education students. The college professors of Teacher Education students moderately utilized gamification strategies . Yet, the students’ level ofmotivation is high. The results revealed that there was no significant relationship between the extent of utilization and learners’ motivation. The researchers nonetheless came to the conclusion that students are highly motivated to learn when gamification is used. Thus, there was a moderate positive correlation between the extent of utilization of gamification strategies and learners' level of motivation, although they were not significantly correlated . Therefore, this study proposes that gamification should be used as a sustainable method to increase the learning motivation of students to ensure quality education.